Program Konservasi Penanaman 1000 Pohon Berbasis Masyarakat di Wilayah Hulu DAS Bedadung Jember: Conservation Program for Planting 1000 Tress Based on Society in the Upstream Area of the Bedadung Jember Watershed - Habriantono, Bakhroini; Alfarisy, Fariz Kustiawan; Suharto, Suharto; Wagiyana, Wagiyana; Nurcahyanti, Suhartiningsih Dwi; Masnilah, Rachmi; Hoesain, Mohammad; Nusantara, Alrio Putra; Hakim, Tiara Oktavia Putri; Lestari, Resti Putri; Risqianti, Riza; Fa'ayunina, Miftakhul; Merina, Gusna; Ramadhani, Farchan Mushaf Al; Putra, Dimas Ganda Permana (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Environmental degradation in the Bedadung Watershed (DAS) in Jember has led to natural disasters such as floods and landslides. A conservation effort through a program of planting 1,000 trees in the upstream area of the watershed was initiated to restore environmental health and improve the welfare of the local community. This program was conducted over nine months in Sucopangepok Village, coordinating with local authorities and residents. The tree seedlings, including Teak, Coffee, Sengon, and Soursop, were provided by BPDASHL Brantas Sampean Jember. Planting was done in vacant land using technical, social, and focus group discussion (FGD) approaches. Active community participation was evident in the planting and maintenance of the trees. The outreach and discussions increased awareness about the importance of conservation and disaster mitigation. Planting economically valuable trees is expected to provide long-term benefits for the environment and the community’s economy. The program results showed a reduction in natural disaster risks and an increase in community awareness and participation. Support from the government, private sector, and non-governmental organizations is crucial to ensure the success and sustainability of this conservation program.